Application of Metallic Nanoparticles and Their Hybrids as Innovative Sorbents for Separation and Pre-concentration of Trace Elements by Dispersive Micro-Solid Phase Extraction: A Minireview - Hagarová, Ingrid; Nemček, Lucia (Frontiers in Chemistry, 2021)
It is indisputable that separation techniques have found their rightful place in current analytical chemistry, considering the growing complexity of analyzed samples and (ultra)trace concentration levels of many studied analytes. Among separation techniques, extraction is one of the most popular ones due to its efficiency, simplicity, low cost and short processing times. Nonetheless, research interests are directed towards the enhancement of performance of these procedures in terms of selectivity. Dispersive solid phase extraction (DSPE) represents a novel alternative to conventional solid phase extraction (SPE) which not only delivers environment-friendly extraction with less solvent consumption, but also significantly improves analytical figures of merit. A miniaturized modification of DSPE, known as dispersive micro-solid phase extraction (DMSPE), is one of the most recent trends and can be applied for the extraction of wide variety of analytes from various liquid matrices. While DSPE procedures generally use sorbents of different origin and sizes, in DMSPE predominantly nanostructured materials are required. The aim of this paper is to provide an overview of recently published original papers on DMSPE procedures in which metallic nanoparticles and hybrid materials containing metallic particles along with other (often carbon-based) constituent(s) at the nanometer level have been utilized for separation and preconcentration of (ultra)trace elements in liquid samples. The studies included in this review emphasize the great analytical potential of procedures producing reliable results in the analysis of complex liquid matrices, where the detection of target analyte is often complicated by the presence of interfering substances.